The Political Legacy of Colonialism in Zimbabwe Implications for Justice and Elections in Africa. - Benyera, Everisto (New York : Routledge, 2025)
This book investigates the political legacy of colonialism in contemporary African institutions. Using the case study of electoral and justice institutions in post-colonial Zimbabwe, the book explores how those in post-colonial states relate to and with institutions initially designed to oppress them and remain structurally and systematically colonial. The book argues that the colonial era colonised the land, knowledge, and minds of Africans, resulting in injustice and epistemicides. The book demonstrates how the critical institutions of elections and justice have been rendered anti-black and toxic. The book calls for Africa to invest in epistemic independence, unencumbered by Western political modernity, and then deploy that independence to build reconstituted institutions, structures, and systems that serve the interests of Africans. This book will be an important read for African policymakers and researchers working on African politics, governance, and international relations.
Keywords: POLITICAL SCIENCE / Political Process / Elections; Justice, Administration of -- Zimbabwe; Elections -- Zimbabwe; Racism against Black people -- Zimbabwe; Zimbabwe -- Colonial influence; Zimbabwe -- Politics and government